Malaysian high-tech industry profiling. SWOT and future research trend - Al-Shami, Samer Ali Hussein; Sidek, Safiah; Adil Abdul Raheem, Hayder; Mohammed Al-Araji, Zaid Jasim; Bakri, Mohammed Hariri (International Research Association for Talent Development and Excellence, 2020)
The study aims to review and discuss the definition of high-tech industry generally and in Malaysian particularly. It also investigates the importance of this industry in Malaysia with discussing the strengths, opportunities, challenges, weaknesses and concluding with the future trend. The finding of this paper confirm that high-tech industry is an important source of Malaysian economic development and has the potential opportunity to dominate the industry in the industrial era 4.0. The government draw the roadmap precipitated by several policies with aiming to transform Malaysian vision to become one of the developed industrial countries. Yet, the transformation process is fraught with several challenges. Generally, the concept of high-tech industry lacks of consensus definition. In addition, Malaysian still reply on multinational corporations as a source of technology and knowledge transfer, meanwhile there is lack of efficiency technology adoption and utilization. Therefore, empirically exploring the technological factors that boost Malaysian high–tech innovativeness and build its capacity is recommended for future research